Recuperação de área de preservação permanente através da nucleação como subsídio à adequação legal da atividade de extração de argila em pequena propriedade - Lemos, Cassia Maria Gama [UNESP] (2015)
This study aimed to analyze the viability of rehabilitation of degraded Permanent Preservation Area (APP) using the nucleation. The study area is located in a rural property that needs the environmental license granted by the Environmental Company of State of São Paulo. In this paper, the proposed of rehabilitation of degraded area considered steps of characterization of the area, natural regeneration monitoring, implementation of the technique chosen and monitoring of this technique. During characterization, the prerequisites for the implementation of nucleation techniques were analyzed. After confirmed the viability of the implementation of nucleation techniques, was chosen soil transposition technique to be implemented and monitored. The monitoring ocurred by five months, after this period, the natural regeneration was observed occurring in the preservation area of the nascent study, and indicative of intense biological activity in the transplanted nucleus. Proven the viability of nucleation technique, it is believed that the project of the recovery of the APP could be developed based on nucleating, because this APP has presence of forest fragment remaining inside the area, little evidence of erosion and development of seedlings in APP after isolation